Infection with Helicobacter Pylori and the Risk of Iron Deficiency Anaemia - Rashid Karim, Wajid Iqbal, Mahwash Mengal, Muhammad Alam Mengal, Muhammad Mohsin Sial, Ahmed Latif Chaudhary, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this research is to determine the frequency of a condition known as iron deficiency anaemia (IDA) among people who have been infected with Helicobacter pylori. Study Design: Cross-sectional/ Prospective study Place and Duration: Hayatabad Medical Complex Peshawar in the duration from November, 2022 to April, 2023. Methods: There were a total of 116 patients with Helicobacter pylori infections, whose ages ranged from 20 to 70. After collecting demographic information from each participant (including age, sex, BMI, education level, and residence), each patient gave written informed consent. Subjects' blood was tested for iron, transferrin saturation, ferritin, which and total iron-binding capacity. Histopathology, stool antigen testing, a fast urease test, and a urea breath test can all diagnose Helicobacter pylori infection. All statistical analyses were performed in SPSS 25.0. Results: There were 74 (63.8%) females and 42 (36.2%) males in our study. Patients mean age was 28.13±14.68 years and had mean BMI 23.6±11.26 kg/m2. The mean Hemoglobin level of the patients was 11.9±1.8 (g/dl), the iron level was 47.11±6.49 (ug/dl) and mean ferritin level was 119.6±32.68 (ng per ml). Among 116 cases, 42 (36.2%) patients had Iron Deficiency Anemia (IDA). Conclusion: An increased incidence of iron deficiency anaemia was seen among individuals with Helicobacter pylori infections; the majority of these patients were adult females. Keywords: H.pylori infection, Prevalence, Iron Deficiency Anemia (IDA),